Clinical relevance of molecular testing methods in the diagnosis and guidance of therapy in patients with staphylococcal empyema: a systematic review and meta-analysis - Suvash Chandra Ojha; Suvash Chandra Ojha; Ke Chen; Ke Chen; Yue Yuan; Sarfraz Ahmed; Aijaz Ahmad Malik; Mehru Nisha; Yun-Jian Sheng; Yun-Jian Sheng; Changfeng Sun; Changfeng Sun; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
BackgroundEfficient detection tools for determining staphylococcal pleural infection are critical for its eradication. The objective of this meta-analysis was to assess the diagnostic utility of nucleic acid amplification tests (NAAT) in suspected empyema cases to identify staphylococcal strains and avoid unnecessary empiric methicillin-resistant Staphylococcus aureus (MRSA) therapy.MethodsFrom inception to July 24, 2021, relevant records were retrieved from PubMed, Embase, Scopus, Web of Science, and the Cochrane Library. The quality of studies was determined using the QUADAS-2 tool. The pooled sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and hierarchical summary receiver operating characteristic (HSROC) curve for NAAT’s diagnostic performance were evaluated using an HSROC model.ResultsEight studies comprising 424 samples evaluated NAAT accuracy for Staphylococcus aureus (SA) identification, while four studies comprising 317 samples evaluated methicillin-resistant Staphylococcus aureus (MRSA) identification. The pooled NAAT summary estimates for detection of both SA (sensitivity: 0.35 (95% CI 0.19–0.55), specificity: 0.95 (95% CI 0.92–0.97), PLR: 7.92 (95% CI 4.98–12.59), NLR: 0.44 (95% CI 0.14–1.46), and DOR: 24.0 (95% CI 6.59–87.61) ) and MRSA (sensitivity: 0.45 (95% CI 0.15–0.78), specificity: 0.93 (95% CI 0.89–0.95), PLR: 10.06 (95% CI 1.49–67.69), NLR: 0.69 (95% CI 0.41–1.15), and DOR: 27.18 (95% CI 2.97–248.6) ) were comparable. The I2 statistical scores for MRSA and SA identification sensitivity were 13.7% and 74.9%, respectively, indicating mild to substantial heterogeneity. PCR was frequently used among NAA tests, and its diagnostic accuracy coincided well with the overall summary estimates. A meta-regression and subgroup analysis of country, setting, study design, patient selection, and sample condition could not explain the heterogeneity (meta-regression P = 0.66, P = 0.46, P = 0.98, P = 0.68, and P = 0.79, respectively) in diagnostic effectiveness.ConclusionsOur study suggested that the diagnostic accuracy of NAA tests is currently inadequate to substitute culture as a principal screening test. NAAT could be used in conjunction with microbiological culture due to the advantage of faster results and in situations where culture tests are not doable.